Urgensi Pendekatan Hermeneutik Dalam Memahami Al-Qur’an - Nikmah, Alfi (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2020)
The way to understand the Qur'an and understand the meaning or content in the Qur'an is to understand the editorial of the Qur'an directly. In this way, we will be able to feel (tadzawwuq) the pulses of the Qur'an's description that are so beautiful and charming. However, because not all Muslims are able to understand the editorial of the Qur'an directly it needs to be translated into other languages. This understanding of the Qur'an uses the study of the hermeneutic method which is from time to time has experienced significant developments in qualitative research, including being a stream of philosophical science and applied in the humanities (social humanitarian) sciences, namely